Edentulismo no Brasil: Tendências, projeções e expectativas até 2040 - Cardoso, Mayra; Balducci, Ivan [UNESP]; Telles, Daniel de Moraes; Lourenço, Eduardo José Veras; Nogueira Júnior, Lafayette [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to examine the edentulism rates in Brazil and make projections for the next years. Data were collected from three national oral health surveys. The percentage of edentulous jaws was calculated. Projections were made for the years 2020, 2030 and 2040, assuming that edentulism follows a logistic function. Population projections were also performed. Annual change in proportion of edentulous jaws was-0.04% for teenagers,-0.96% for adults and 0.76% for the elderly. By 2040, edentulous jaws will be virtually zero among teenagers, 1.77% among adults and 85.96% among the elderly. Teenagers will slightly decrease in number; adults will increase and subsequently decrease; the elderly will continue to increase. In teenagers and adults, the number of edentulous jaws will decrease, being approximately 616,000 in 2040. In the elderly, it will increase alarmingly, reaching over 64 million in 2040. Edentulism is declining in Brazil among teenagers and middle-aged adults, but is still increasing and will continue to increase for the next decades among the elderly.
Edentulism in Brazil: Trends, projections and expectations until 2040
Keywords: Epidemiology; Health statistics; Oral health; Public health; Tooth loss